2008
DOI: 10.1177/1933719108316911
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals Putative HOXA10 Downstream Targets in the Periimplantation Mouse Uterus

Abstract: HOXA10 encodes a transcription factor required for endometrial receptivity and embryo implantation. The objective of this study was to identify and to characterize those molecular markers regulated by HOXA10 expression. The authors have identified putative HOXA10 target genes identified by microarray analysis employing a murine model of transient HOXA10 expression during the anticipated implantation window. Microarray analysis identified 40 statistically significant genes regulated by HOXA10 overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…They are both regulated and/or modulated by the sex steroid progesterone (45). A recent microarray-based study from our laboratory identified the GABA A subunit as a potential Hoxa10 target gene in the murine endometrium (45). Here we demonstrate that not only was GABA A subunit gene expression regulated by HOXA10, its membrane translocation was as well.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…They are both regulated and/or modulated by the sex steroid progesterone (45). A recent microarray-based study from our laboratory identified the GABA A subunit as a potential Hoxa10 target gene in the murine endometrium (45). Here we demonstrate that not only was GABA A subunit gene expression regulated by HOXA10, its membrane translocation was as well.…”
supporting
confidence: 51%
“…Both HOXA10 and GABA A subunit receptors are expressed in the endometrium at the time of embryonic implantation (21). They are both regulated and/or modulated by the sex steroid progesterone (45). A recent microarray-based study from our laboratory identified the GABA A subunit as a potential Hoxa10 target gene in the murine endometrium (45).…”
mentioning
confidence: 99%
“…Some of these implicated genes include: urocortin [18], IL-15 [19], HOXA10 (homeobox A10) [20], and leukemia inhibitory factor [21]. It is plausible then that FOXO1 may be included with urocortin, IL-15, HOXA10, and leukemia inhibitory factor as a contributor to the progression of stromal cell decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial ␤ 3 -integrin subunit gene expression is directly upregulated by HOXA10 (13). cDNA microarray has recently been used to broadly search for potential downstream targets of HOXA10 (24,45). When HOXA10 was overexpressed, several target genes were found to have significantly increased expression.…”
mentioning
confidence: 99%
“…When HOXA10 was overexpressed, several target genes were found to have significantly increased expression. Of these, the largest increase was in the tryptophan 2,3-dioxygenase (TDO) gene that increased eightfold in response to constitutive expression of HOXA10 (45).…”
mentioning
confidence: 99%